Advantages of robot-assisted PKP under local anesthesia in the treatment of OVCF: a retrospective, non-randomized, controlled, clinical study - Xue, Han; Liu, Wei; Li, Ruochen; Xiao, Fengxu; Zhu, Zheyue; Wu, Guangwei; Zhang, Chen (Frontiers in Surgery, 2024)
Background: Robot-assisted technology has been widely used in orthopedic surgery, which can provide surgeons with higher accuracy and reduce radiation exposure. In spinal surgery, robots are often used to assist pedicle screw implantation, while there are relatively few studies on robot-assisted percutaneous kyphoplasty (PKP) under local anesthesia. Methods: A total of 96 patients with single-segment OVCF who met the inclusion criteria were included in this study. Fifty-six patients underwent robot-assisted PKP and forty patients underwent conventional PKP by the same group of surgeons. Collect the relevant parameters. Results: The puncture time and fluoroscopy times during puncture in the robot group were significantly less than those in the manual group (P<0.001). The success rate of first puncture in the robot group was 92.5%. Conclusions: PKP under local anesthesia assisted by the new spinal surgical robot effectively reduces the patient's intraoperative discomfort and has a low learning curve.